Population and home range of the West Java Black Langur (Trachypithecus mauritius) in the forested area of Taman Safari Indonesia - Manansang, Jansen; Sinaga, Walberto; Mansjoer, Sri Supraptini (Foresty Faculty of Hasanuddin University, 2023)
The West Java black langur (Trachypithecus mauritius) is an Indonesian endemic primate found on the island of Java. Status and Conservation of the species is classified as Vulnerable based on the IUCN Red List and is listed in Appendix 2 of CITES. The West Javan langurs have been protected by Indonesian law since 1999. Under the decree of the Minister of Environment and Forestry Number. P.106/MENLHK/SETJEN/KUM.1/12/2018. The study aimed to examine population the population of the species and to determine its home range the forested area of Taman Safari Indonesia Bogor. This research was carried out from January to September 2021. Method The data collection used was a combination of methods concentrated Concentration Count using the observation method directly in the field. Analyze population distribution patterns using Nearest Neighbors, while the population distribution was analyzed using the area of the outermost point of encounter. The results showed that there were two groups of the West Java black langur existed in the area. The first group was around the location of the two houses, the panda palace, and the Jaksa waterfall 32 individuals and the second group was consisted of 15 individuals. Based on the survey, it was estimated that with an population density of T. mauritius in the area was 0.18 individuals/km² while the group density was 0.008 group/km². Group I was known to have a home range area of 17 ha while Group II had larger home range with 25 ha. The West Java black langur in this area were found to inhabit the upper parts of the forest at the altitude of 1000 to 1550 m above sea level. Population distribution patterns classified as clustered in all West Java black langur groups. The distribution of the West Java black langur population in TSI Bogor covers 58% of the total area.